Evaluasi Toleransi Plasma Nutfah Padi terhadap P Rendah di Tanah Sawah - Abd. Aziz Syarif; Didy Sopandie; M. A. Chozin; K. Idris; Suwarno Suwarno (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2010)
A field experiment was conducted to assessgenotypic variability of tolerance and to identify tolerantgenotypes to low phosphorus (P) among rice germplasm onlowland (paddy) rice field with low available and potential Pusing strip plot design with three replications. P fertilization(with and without added P) was assigned as horizontal factorand 120 rice plant genotypes as vertical factor. Data on plantheight, tiller number, and shoot dryweight were collected. LowP tolerance was judged by relative value i.e. observation valueat the plot without P treatment devided by the value at the plotwith P treatment. The judgement was determined based onIRRI standard. Shoot P uptake of five tolerant and fivesensitive genotypes on no added P treatment was alsoobserved. The results showed that the germplasm exhibitedphenotypic and genotypic variability of low P tolerance. Thehighest genotypic variability of tolerance was shown by thevalue based on relative tillering number (28.7%), followed bythat of relative shoot dryweight (22,6%) and relative plantheight (7,6%). The highest broadsense heritability of tolerancewas shown by the value based on relative tiller number(24.1%), followed by that of relative plant height (16.6%) andrelative shoot dry weight (15.0%) Fourteen genotypes wereidentified as highly tolerant based on relative tiller number and28 genotypes based on relative shoot dryweight. The toleranceof genotype was attained by higher P uptake and higherinternal use efficiency.